Diet of longnose stingray Hypanus guttatus (Myliobatiformes: Dasyatidae) in tropical coastal waters of Brazil - Gianeti, Michel Donato; Yokota, Leandro [UNESP]; Lessa, Rosangela Paula Teixeira; Dias, June Ferraz (My University, 2019)
This study investigated the diet of longnose stingray Hypanus guttatus in the tropical waters of north-eastern Brazil. Samples were obtained from monthly sampling of artisanal fisheries from August 2007 to July 2008. A total of 258 specimens were examined, 127 females and 131 males, and stomach contents analysis suggested H. guttatus to be a generalist and opportunistic predator feeding on the most available prey in the environment. There was no significant difference in the diet composition of males and females, or between seasons. However, an ontogenetic dietary shift was observed with larger individuals having an increased proportion of molluscs in the diet, whilst smaller individuals predated primarily on small crustaceans.
Keywords: Diet; Hypanus guttatus; north-eastern Brazil